2019
DOI: 10.3389/fpls.2019.01367
|View full text |Cite
|
Sign up to set email alerts
|

SmGRAS1 and SmGRAS2 Regulate the Biosynthesis of Tanshinones and Phenolic Acids in Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza is one of the most widely used traditional Chinese medicinal plants because of its excellent performance in treating heart diseases. Tanshinones and phenolic acids are two important classes of effective metabolites, and their biosynthesis has attracted widespread interest. Here, we functionally characterized SmGRAS1 and SmGRAS2, two GRAS family transcription factors from S. miltiorrhiza. SmGRAS1/2 were highly expressed in the root periderm, where tanshinones mainly accumulated in S. miltior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…This result also explains a series of composition content changes in the hairy root of S. miltiorrhiza at the transcriptional level after GA treatment, such as the increased tanshinones and phenolic acids contents. In addition, since our previous research found that 3 SmGRAS genes can promote the biosynthesis of tanshinones and inhibit the biosynthesis of GA, we hypothesize that GRAS core regulators of the GA signaling pathway would be involved in the regulation of GA on the secondary metabolism [ 24 , 25 ]. Therefore, we also deeply analyzed the expressions of DEGs in the GA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result also explains a series of composition content changes in the hairy root of S. miltiorrhiza at the transcriptional level after GA treatment, such as the increased tanshinones and phenolic acids contents. In addition, since our previous research found that 3 SmGRAS genes can promote the biosynthesis of tanshinones and inhibit the biosynthesis of GA, we hypothesize that GRAS core regulators of the GA signaling pathway would be involved in the regulation of GA on the secondary metabolism [ 24 , 25 ]. Therefore, we also deeply analyzed the expressions of DEGs in the GA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ten DEGs specific primers were designed by primer 5 (Table S5 ). qRT-PCR was performed on a real-time PCR system (Bio-Rad CFX96, USA), according to our previous methods [ 24 ]. The SmActin gene was used as the endogenous control [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get a better understanding of evolutionary relationships, a neighbor-joining phylogenetic tree was constructed among GRFs from Arabidopsis (9), soybean (22), rice (12) poplar (19), and four Rosaceae species (46). As shown in Fig.…”
Section: Phylogenetic and Structural Analyses Of Grf Genesmentioning
confidence: 99%
“…Supplementary Table S3). In this area we quali cated many other important potential cis-elements, such as GARE motif and P-box (GA responsive element), a CAT-box (cis-acting regulatory element related to meristem expression), AuxRR-core and TGA-element (auxin-responsive element), an RY element (seedspeci c regulation) and a TC-rich repeats (defense and stress responsiveness) [46][47][48][49][50][51]. GARE, P-box, CATbox, AuxRR-core, TGA-element, RY element and TC-rich repeats were distributed within 3, 3, 7, 2, 3, 1 and 5…”
Section: Analysis Of Cis-elements In the Promoter Sequences Of Ppgrf mentioning
confidence: 99%